A new method for calculation of short time-step g-functions of vertical ground heat exchangers. (25th April 2016) - Wei, Jianping; Wang, Lei; Jia, Lei; Cai, Wenjian
Highlights: A method to simplify the CMILS model of vertical GHE was proposed. G-function was easily implemented and quickly calculated by proposed method. Experimental verification was made through a reported reference data. Comparison studies showed that the proposed method had a good performance. Abstract: The composite medium infinite line source model (CMILS) was recently developed to describe the heat transfer of borehole ground heat exchanges. But this model is very complicated and time-consuming to calculate the solutions, which limit its practical applications. This paper presents a method to simplify the CMILS model and develops short time-step response g-functions using the simplified CMILS model. The advantage of the new short time-step response g-functions is that they are simple in calculation with comparable accuracy compared with CMILS model. Simulation studies show that g-functions calculated by simplified CMILS model match nicely with the experimental data. Detailed comparisons are also carried out between the simplified CMILS model and other numerical or analytical models through simulation.